Pendekatan Guru Profesional dalam Mengatasi Hambatan Belajar pada Pembelajaran Sejarah Kebudayaan Islam - Kholik, Moh.; Muslih, Imam; Santoso, Mohamad Puji; Himami, Shoviyul; Azizah, Mar'atul (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study examines the professionalism of teachers in overcoming student learning difficulties in the subject of Islamic Cultural History (SKI) at MTsN 4 Mojokerto. Using a qualitative approach with a case study research type, this study aims to analyze innovative strategies applied by teachers in facilitating effective SKI learning. Data collection was conducted through in-depth interviews, participant observation, and documentation studies, with data analysis using the Miles and Huberman interactive model. The results show that SKI teachers apply high professionalism through careful lesson planning and implementation of comprehensive learning strategies. The main strategies include a student-oriented approach, inquiry/discovery learning, and integrating various learning resources. Teacher professionalism is reflected in the ability to analyze class situations, the use of varied learning methods, and the use of diverse learning media. The implementation of this strategy shows a positive impact on SKI learning, characterized by increased student interest in learning and the creation of a conducive learning atmosphere. This success is supported by teachers' commitment to continuous professional development and adequate institutional support from the school.